Peran Guru Agama dalam Menanamkan Nilai-Nilai Pancasila pada Peserta Didik MI DDI Mareto Kabupaten Barru - Alam, Nur (AIJER: Algazali International Journal Of Educational Research, 2024)
Abstract: This study aims to determine the values of Pancasila, determine the role of religious teachers, determine the challenges of religious teachers in instilling Pancasila values to MI DDI Mareto students in Barru Regency. The research applied a descriptive qualitative approach. This research uses a qualitative case study approach, which is a series of scientific activities carried out intensively, in detail and in depth about a program, event, and activity, either at the level of an individual, group of people, institution, or organization to gain in-depth knowledge about the event. Research subjects were all religion teachers in Madrasah Ibtidaiyah, namely Aqidah, SKI, Qur'an Hadith and Islamic Cultural History Subject Teachers. The results showed that religious teachers must integrate Pancasila values in learning materials by linking Islamic teachings with the values of justice tolerance, cooperation values when teaching zakat material. Religion teachers play a role in instilling Pancasila values. This role is modeled by students. The main challenge faced by religious teachers in instilling Pancasila values is determining a special strategy so that students understand religious subjects and understand Pancasila values in the learning process. The next challenge is the teachers.